Avaliação do efeito da temperatura dos sistemas adesivos na resistência de união à dentina - Machado, Patrícia (2012)
The establishment of a routine of use of adhesive systems in dentistry make an essential way to seek out the best characteristics of these materials in order to optimizes the clinical results. The aim of this study was to evaluate the effect of temperature of adhesive system on bond strength to dentin. A total of 120 caries free third molars were sectioned longitudinally in order to obtain 240 hemi-teeth. They were embedded into a PVC cylinder with acrylic resin and polished with silicon carbide sandpapers in sequential decreasing in order to produce a standardized smear layer. The specimens were divided into 24 groups (n=10), and each one was treated with 4 different adhesive system (Adper Single Bond 2, 3MESPE; XP Bond, Dentsply; Stae, SDI; Admira, Voco) at 3 temperatures (5°C, 20°C e 37°C), simulating the follow conditions: refrigerator storage, environmental temperature and body temperature, respectively. Composite resin restorations were built up into a starch matrix bonded on dentin. After removal of the matrix, the samples were stored in distilled water at 37°C. The specimens were submitted to microshear test in a universal testing machine (EMIC DL 1000 Equipamentos e Sistemas de Ensaio Ltda. São José dos Pinhais, PR, Brasil) in times of storage of 24 hours and 180 days. The ANOVA indicated that factors like adhesive system (p<0,001), temperature (p<0,001) and storage time (p<0,015) affect significantly the bond strength, as well interactions between the factors. The most frequent behavior was increasement of bond strength according to the higher temperature.